Lexicography and New Testament Categories of Church Discipline - Clarke, Andrew D. (Tyndale bulletin, 2013)
A range of circumstances, which were formative in the crises prompting the Protestant Reformation, resulted in heightened emphasis on ecclesiastical discipline, with some Reformation Confessions elevating discipline ‘according to the Word of God’ to one of three significant ‘marks’ of the ‘true church’. However, the Bible prompted no similar consensus among either the Reformers or the Reformation Confessions as to how, when, by or to whom such discipline should be exercised. Although the New Testament has no dominant vocabulary for ‘discipline’, the fixing on this term in the Sixteenth Century and subsequently nonetheless became a controlling principle in identifying and interpreting certain New Testament passages as ‘disciplinary’ in focus. Latin lexical roots pose an additional disjunction between first-century and post-Reformation legacy understandings of ‘discipline’. Revisiting New Testament categories of discipleship, education and Christian formation may offer a constructively holistic approach that reaches beyond now traditional views of church discipline.